Coulomb interactions between dipolar quantum fluctuations in van der Waals bound molecules and materials - Martin Stöhr (Nature Portfolio, 2021)
High-level methods to describe van der Waals interactions are limited due to their computational cost. This work introduces a new theoretical approach, that extends the dipolar many-body dispersion formalism to higher-order contributions, demonstrated to be applicable to practically-relevant systems and nano-environments.